flavonoids from Fissistigma acuminatissima - Van, Nguyen Hong; Thuy, Trinh Thi; Sung, Tran Van (Vietnam Journal of Chemistry, 2014)
From the leaves of Fissistigma acuminatissima growing in Vietnam, two flavonoids, catechin and isorhamnetin-3-o-rutinoside were isolated. Their structures were characterized on the basis of MS and NMR spectra data and comparison with reported data.Keywords: Annonaeae; Fissistigma acuminatissima; catechin; isorhamnetin-3-o-rutinoside.